Applying Note-taking strategies to develop high school students’ listening skill – A quasi-experimental Research at Van Xuan – Hoai Duc high school: . M.A Thesis - Phí, Thị Bích (ĐHNN, 2017)
M.A. Thesis -- ĐHNN. Vietnam National University, Hanoi, 2013